1998
DOI: 10.1287/opre.46.6.749
|View full text |Cite
|
Sign up to set email alerts
|

A Multiattribute Utility Analysis of Alternatives for the Disposition of Surplus Weapons-Grade Plutonium

Abstract: This paper describes an application of multiattribute utility theory to support the selection of a technology for the disposition of surplus weapons-grade plutonium by the Department of Energy (DOE). This analysis evaluated 13 alternatives, examined the sensitivity of the recommendations to the weights and assumptions, and quantified the potential benefit of the simultaneous deployment of several technologies. The measures of performance that were identified through the creation of a hierarchy of objectives he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 7 publications
0
31
0
1
Order By: Relevance
“…They investigated three classification approaches, including a heuristic pattern-recognition method, classification trees, and discriminant analysis. Dyer et al (1998) and Butler et al (2005) addressed the problem of disposing of weapons-grade plutonium. Dyer et al (1998) used multiple attribute utility theory (MAUT) to develop a hierarchy of objectives, to evaluate 13 alternatives, and to conduct sensitivity analyses.…”
Section: Countermeasures Portfoliosmentioning
confidence: 99%
See 1 more Smart Citation
“…They investigated three classification approaches, including a heuristic pattern-recognition method, classification trees, and discriminant analysis. Dyer et al (1998) and Butler et al (2005) addressed the problem of disposing of weapons-grade plutonium. Dyer et al (1998) used multiple attribute utility theory (MAUT) to develop a hierarchy of objectives, to evaluate 13 alternatives, and to conduct sensitivity analyses.…”
Section: Countermeasures Portfoliosmentioning
confidence: 99%
“…Dyer et al (1998) and Butler et al (2005) addressed the problem of disposing of weapons-grade plutonium. Dyer et al (1998) used multiple attribute utility theory (MAUT) to develop a hierarchy of objectives, to evaluate 13 alternatives, and to conduct sensitivity analyses. Butler et al (2005) used MAUT to help the US and Russia to evaluate alternatives for disposing of stockpiles of weapons-grade plutonium.…”
Section: Countermeasures Portfoliosmentioning
confidence: 99%
“…An exhaustive set of research articles demonstrating results of initiative studies may be found in the journals and web-sites which give an overview on the experience gained with the MCDM methods and tools application in the nuclear engineering area (see, for example, [17][18][19][20][21][22][23][24]). Some of them will be discussed in the following section.…”
Section: Research Articles and Initiative Studiesmentioning
confidence: 99%
“…The MODA is defined as an approach to decision making under conditions of complexity, with inherent uncertainty, multiple objectives and different perspectives towards the decision problem [17]. This approach has been successfully used in other fields [18][19][20][21]. The MODA approach is based on the Simple Multi-Attribute Rating Technique (SMART) of Edwards [22] and is often used in comparative studies when alternative design options are available.…”
Section: Multi-objectives Decision Analysis and Risk Assessmentmentioning
confidence: 99%